B. Transform the following vertex form y = a(x – h)? + k, to general form( y = ax2 + bx + c)., 1.y=3(x-2)\xb2+4, 2.y=(x-2)\xb2+6, 3.y=3(x-2)\xb2+4, 4.y=2(x+2)\xb2-3, 5.y=-2(x+6)\xb2-3,

Posted on


B. Transform the following vertex form y = a(x – h)? + k


to general form( y = ax2 + bx + c).

1.y=3(x-2)²+4
2.y=(x-2)²+6
3.y=3(x-2)²+4
4.y=2(x+2)²-3
5.y=-2(x+6)²-3

GIVEN⤵️

1. y=3(x-2)²+4

2. y=(x-2)²+6

3. y=3(x-2)²+4

4. y=2(x+2)²-3

5. y=-2(x+6)²-3

SOLUTION⤵️

1. y=3(x-2)²+4

y=3(x²-4x+4)+4

y=3x²-12x+12+4

y=3x²-12x+16 ✔️

2. y=(x-2)²+6

y= x²-4x+4+6

y= x²-4x+10 ✔️

3. y=3(x-2)²+4

y=3(x²-4x+4)+4

y=3x²-12x+12+4

y=3x²-12x+16 ✔️

4. y=2(x+2)²-3

y=2(x²+4x+4)-3

y=2x²+8x+8-3

y=2x²+8x+5 ✔️

5. y=-2(x+6)²-3

y=-2(x²+12x+36)-3

y=-2x²-24x-72-3

y=-2x²-24x-75 ✔️

ANSWER⤵️

1. y=3x²-12x+16

2. y= x²-4x+10

3. y=3x²-12x+16

4. y=2x²+8x+5

5. y=-2x²-24x-75

#CarryOnLearning


Leave a Reply

Your email address will not be published.